Pengarusutamaan Gender dan Perlindungan Anak dalam Kebijakan Daerah Kabupaten Wonogiri Ditinjau dari Perspektif Hukum Tata Negara - Windari Windari; Ruslina Dwi Wahyuni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
Gender mainstreaming and child protection are fundamental principles in the implementation of regional governance based on the constitution and laws and regulations. Wonogiri Regency, as part of the regional government system, has a constitutional obligation to integrate gender perspectives and the best interests of children into every regional policy. This article aims to analyze the implementation of gender mainstreaming and child protection in Wonogiri Regency regional policies from the perspective of Constitutional Law, and to identify their conformity with the principles of the rule of law, regional autonomy, and the protection of human rights. The research method used is normative legal research with a legislative approach and a conceptual approach. Data were obtained through a literature review of relevant laws and regulations, legal doctrines, and regional policies. The results of the study indicate that gender mainstreaming and child protection in Wonogiri Regency have normatively obtained an adequate legal basis, both at the national and regional levels, but in practice still face various obstacles, including weak coordination between regional agencies, budget constraints, and the suboptimal integration of gender and child protection principles in policy formulation and implementation. Therefore, it is necessary to strengthen the commitment of regional governments, harmonize regional regulations, and effective constitutional oversight so that gender mainstreaming and child protection can be implemented optimally in accordance with the principles of Constitutional Law and sustainable development goals.